Assessment of road traffic noise: a case study in Monastir City - Chebil, Jalel; Ghaeb, Jasim; Fekih, Mohamed Anwer; Habaebi, Mohamed Hadi (Hashemite University, Jordan, 2019)
In the last two decades, Tunisia has witnessed a sharp increase in the number of vehicle users which gave rise to higher road traffic noise levels especially in urban areas. This type of noise causes adverse effect on humans, such as sleeping disorder, annoyance, hearing disorder, etc. Therefore, it is crucial to evaluate traffic noise levels in populated areas in order to highlight problematic areas, so that architects and engineers can find solutions to reduce noise impacts. This paper presents a case study of traffic noise levels at four main roads in the city of Monastir- Tunisia and it also investigates the performance of traffic noise models. In the first part, it is found that the measured noise is mostly due to traffic noise and its levels exceeded the limits recommended by both the World Health Organization (WHO) and the Tunisian environmental standards. In the second part, the study compares the performance of five known traffic noise models: Griffith and Langdon, Burgess, French CSTB (Centre Scientifique et Technique du Batiment), Fagotti and the Italian CNR (Consiglio Nazionale delle Ricerche). It found that the French CSTB model outperforms the others when applied to the measured sites.